2011
DOI: 10.1534/g3.111.000703
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping and Candidate Gene Analysis of Telomere Length Control Factors in Maize (Zea maysL.)

Abstract: Telomere length is a quantitative trait important for many cellular functions. Failure to regulate telomere length contributes to genomic instability, cellular senescence, cancer, and apoptosis in humans, but the functional significance of telomere regulation in plants is much less well understood. To gain a better understanding of telomere biology in plants, we used quantitative trait locus (QTL) mapping to identify genetic elements that control telomere length variation in maize (Zea mays L.). For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 110 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…Burr et al (1992) initially showed variation of telomere length within maize RIL populations (Burr et al 1992). QTL mapping in maize later identified a number of contributing loci and suggested a rad51-like protein as a candidate (Brown et al 2011). QTL from this study, however, are not confirmed experimentally with NILs, and candidates are selected from large QTL regions that are not fine-mapped.…”
Section: Discussionmentioning
confidence: 86%
“…Burr et al (1992) initially showed variation of telomere length within maize RIL populations (Burr et al 1992). QTL mapping in maize later identified a number of contributing loci and suggested a rad51-like protein as a candidate (Brown et al 2011). QTL from this study, however, are not confirmed experimentally with NILs, and candidates are selected from large QTL regions that are not fine-mapped.…”
Section: Discussionmentioning
confidence: 86%
“…In shorter lived model plants and crops Arabidopsis thaliana, Oryza sativa (rice), and Zea mays (maize) telomere lengths are between 2-5 kb, 5-20 kb, and 6-25 kb respectively. In addition, there is variability among telomere lengths across different accessions within a species, while length is conserved within an accession (Shakirov and Shippen, 2004;Brown et al, 2011;Fulcher et al, 2015;Choi et al, 2021). Telomere length in plants has been associated with life history traits including seasonal and phenotypic variation, environmental interactions, sex, flowering time, and seed quantity (Liu et al, 2007;Mu et al, 2014;Choi et al, 2021;Osnato, 2021;Campitelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In maize, only a subset of chromosomes showed telomere labeling. The maize line B73 has a short telomere size of approximately 2.3 kb [Brown et al, 2011]. In soybean, the telomere size ranges from 13 to 18 kb [Kolchinsky and Gresshoff, 1993].…”
Section: Discussionmentioning
confidence: 99%